Potential role of autofluorescence imaging in determining biopsy of oral potentially malignant disorders: A large prospective diagnostic study. (November 2019) - Shi, Linjun; Li, Chenxi; Shen, Xuemin; Zhou, Zengtong; Liu, Wei; Tang, Guoyao
Highlights: The diagnostic value of VELscop was examined in a large prospective study of 517 patients with OPMD. High NPV and sensitivity were in distinguishing high-risk lesions from low-risk lesions. Our data indicate the cases without LAF substantially rule out the presence of high-risk lesions. A no biopsy strategy may be appropriate for OPMD without LAF using VELscope. Abstract: Autofluorescence examination of oral tissues using the VELscope has been suggested as an adjunctive tool for cancer detection and diagnosis. This study aimed to determine the diagnostic value of VELscope in a large prospective study of 517 patients with oral potentially malignant disorders (OPMD). For the outcome assessments of discrimination of carcinoma form general OPMD and distinguishing high-risk lesions (moderate/severe dysplasia and carcinoma) from low-risk lesions (no/mild dysplasia), high sensitivity (100% and 95.9% respectively) and negative predictive value (100% and 98.2% respectively) were observed. All the carcinoma and showed loss of autofluorescence (LAF) and only 3 (0.6%) moderate/severe dysplasia were observed without LAF. These data indicate that the cases without LAF using VELscope substantially rule out the presence of high-risk lesions including cancer. This may prove to be useful specially to alleviate patient anxiety regarding a clinically suspicious oral lesion without the LAF, and to avoid a unnecessary biopsy for these cases. Collectively, a perspective to highlight was that a no biopsy strategy may be appropriate for OPMD without LAF using VELscope after conventional oral examination.